Efektivitas Tipe Pembelajaran Clinical Skill Lab pada Fase Preklinik dalam Pembentukan Keterampilan Klinik Mahasiswa Kedokteran - Lutfiah Hanani; Sabrina Earley Almufit; Giska Tri Putri; Maya Ganda Ratna (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
The preclinical phase is crucial stage in preparing medical students for clinical practice, as students are required not only to master theoretical concepts but also to apply them accurately and safely. One important educational strategy at this stage is Clinical Skill Lab (CSL), which serves as a bridge between theory and clinical practice within safe and controlled learning environment. Through CSL activities, students are expected to develop psychomotor skills, clinical reasoning, and professional confidence before interacting directly with patients. This study aimed to evaluate the effectiveness of various CSL learning models, including Self-Directed Learning (SDL), video-based learning media, and Peer-Assisted Learning (PAL), in improving medical students’ clinical competence. A narrative literature review approach was employed. Data were obtained from the PubMed, Google Scholar, and ScienceDirect databases, covering publications from 2016 to 2025, and six relevant articles were systematically analyzed. The findings indicate differences in effectiveness among the learning methods. SDL was found to be less effective when applied independently due to limited supervision and minimal feedback. Video-based learning was shown to enhance visual understanding and memory retention but tended to be passive. In contrast, PAL emerged as the most effective approach, as it promotes active interaction and provides immediate feedback.